Heterofucans from the brown seaweed Canistrocarpus cervicornis with anticoagulant and antioxidant activities - Camara, Rafael Barros Gomes (2011)
Fucan is a term used to denominate a family of sulfated polysaccharides rich in sulfated L-fucose. We extracted six fucans from Canistrocarpus cervicornis by proteolytic digestion followed by sequential acetone precipitation. These heterofucans are composed mainly of fucose, glucuronic acid, galactose and sulfate. No polysaccharide was capable of prolonging prothrombin time (PT) at the concentration assayed. However, all polysaccharides prolonged activated partial thromboplastin time (aPTT). Four sulfated polysaccharides (CC-0.3/CC-0.5/CC-0.7/CC-1.0) doubled aPTT with only 0.1 mg/mL of plasma, only 1.25-fold less than Clexane®, a commercial low molecular weight heparin. Heterofucans exhibited total antioxidant capacity, low hydroxyl radical scavenging activity, good superoxide radical scavenging efficiency (except CC-1.0), and excellent ferrous chelating ability (except CC-0.3). These results clearly indicate the beneficial effect of C. cervicornis polysaccharides as anticoagulants and antioxidants. Further purification steps and additional studies on structural features as well as in vivo experiments are needed to test the viability of their use as therapeutic agents